The role of NGOs’ microcredit program on rural women’s poverty eradication and empowerment: Investigation from rural areas of Bangladesh - Biddut Kumar Ghosh; Manower Hossain (National Geographical Journal of India, 2023)
The paper focuses on the effectiveness of NGOs’ regarding income-generating activities, the decision-making process, women-related issues such as health and empowerment, and political and legal challenges affecting rural women as they are the most disadvantaged group in society living in deplorable poverty, which is one of the main reasons for women’s disempowerment in Bangladesh. Through the provision of microcredit, NGOs’ are considerably reducing poverty in Bangladesh by giving the underprivileged access to options for income production and self-employment. The present research aims to identify the role of NGOs’ in poverty eradication and to analyze rural women’s socio-economic empowerment as the outcome of microcredit interventions. To conduct the study, primary and secondary data are used. The result shows that women contribute more to household income and can participate in decision-making after receiving and using microcredit. The socio-economic condition and empowerment situation of rural women improved from the loans received from the NGOs but also due to additional training and making them more aware of education and modern technology regarding income generating.